Nikah dan Rujuk di KUA Samarinda: Implementasi Peraturan Pemerintah Nomor 48 Tahun 2014 Tentang Tarif Atas Jenis Penerimaan Negara Bukan Pajak - Furqan, Ana Amalia (Mazahib, 2016)
The implementation of Government Regulation No. 48 Year 2014 concerning the Tariff of Non Tax Revenue which revises the Government Regulation No. 47 of 2004 has become an important topic in marriage bureaucracy in Indonesia. Changes in these regulations include the rate or cost of marriage and marriage reconciliation, from IDR 30,000, - to IDR 600,000, - as long as the marriage solemnization is performed outside the Religious Affairs Office (KUA) or beyond the KUA business hours. As for marriage solemnization performed in the KUA, the charge fee is IDR 0.00. This zero rupiah rate also applies to citizens who are economically less fortunate as well as victims of disasters. After one year of Â its implementation, some questions arise regarding the efficacy of these regulations. By employing three case studies of KUAs in Samarinda Seberang district as a research strategy, this study aims to assess how far is the implementation of the regulation in the KUAs and what sorts of constraints encountered. The study finds that all of the procedures of payment and the cost of marriage and marriage reconciliation in the three KUAs of Samarinda Seberang is in accordance with the provisions of the regulation. However, there are two main obstacles experience: first, the time period for cashing marriage and marriage reconciliation fee is pretty long that it renders difficult for the KUAs to function; second, the lack of marriage registrars who serve in every KUA in Samarinda. These obstacles are needed to be addressed by the Ministry of Religious Affairs in order to better serve the society. Keywords: mariage and mariage reconciliation in Indonesia, Religious Affairs Office in Samarinda, Government Regulation No. 48 Year 2014 concerning the Tariff of Non Tax Revenue.